Développement d’un site web pour le vente sur offre - Haba, Abdallah (university of eloued جامعة الوادي, 2015)
المشروع هو موقع لترتيب الصفقات للبيع عن طريق الانترنت. لأنها تتيح للباعة لعرض بضائعهم على الموقع وللمشترين لمعرفة معلومات البائع وسعر العرض . والتفاعل بين البائعين والمشتريين وتتم عملية البيع مرة واحدة على أن يتفق البائع و المشتري على السعر. The Project is a website to arrange deals on sales transaction. It allows sellers to display their article on the site and for the buyers to see the Seller and offer their price .The site provides interaction between sellers and buyers, the sale transaction is done once that they (buyer and seller) agree on the price
licence mémoire informatique